2013
DOI: 10.1177/0954408912469902
|View full text |Cite
|
Sign up to set email alerts
|

Classifier fusion of vibration and acoustic signals for fault diagnosis and classification of planetary gears based on Dempster–Shafer evidence theory

Abstract: Nowadays, the ever increasing need for higher accuracy, reliability and security in modern industries has given rise intensively to the use of multi-sensor data fusion method in fault diagnosis of industrial equipment. In this article, an effective and powerful method for precise fault diagnosis of planetary gearbox based on fusion of vibration and acoustic data using the Dempster–Shafer theory is presented. For this purpose, the vibration and acoustic signals in different modes of the gears were first receive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(29 citation statements)
references
References 25 publications
2
27
0
Order By: Relevance
“…It should be noted that after testing different signal processing methods such as discrete wavelet transform (DWT), it was found that the best recognition accuracy was achieved by applying these features to the de-noised signals in time-domain, as also reported in [26]. The 17-feature parameters are shown in Table 3 [27]. It is noted that these features can be used for fault diagnosis of all mechanical components, and do not belong a specific system.…”
Section: Feature Extractionmentioning
confidence: 92%
See 1 more Smart Citation
“…It should be noted that after testing different signal processing methods such as discrete wavelet transform (DWT), it was found that the best recognition accuracy was achieved by applying these features to the de-noised signals in time-domain, as also reported in [26]. The 17-feature parameters are shown in Table 3 [27]. It is noted that these features can be used for fault diagnosis of all mechanical components, and do not belong a specific system.…”
Section: Feature Extractionmentioning
confidence: 92%
“…The most important layer in ANN design is hidden layer that should be defined by trial and error [27]. The number of hidden layer neurons can be determined by iterative or random selection.…”
Section: Artificial Neural Network (Ann)mentioning
confidence: 99%
“…Yibo et al in [3] have demonstrated the effectiveness of data fusion between vibration and oil analysis using D-S with BPA from BPNN output and for fault diagnosis of gear box. While Khazaee et al in [4] have reported an increase of accuracy in machinery fault diagnosis via ANN-…”
Section: Nn In D-s Applicationmentioning
confidence: 99%
“…Methods of fusing multiple signals for condition monitoring purposes have been reported by Safizadeh and Latifi [2], who fused vibration and load signals to diagnose bearing faults in induction motors, Khazee et al [3], who combined vibration and acoustic signals to diagnose faults in gears, Yang and Kim [5], who fused vibration and current signals and Loutasa et al [6], who combined vibration, acoustic and oil-debris signals to diagnose faults in gears. In each case, data fusion was shown to increase the accuracy of the system.…”
Section: Introductionmentioning
confidence: 99%
“…Recently several new condition monitoring methods have been developed, which fuse different types of signals in order to achieve better accuracy in identifying faults. It has been observed in multiple works (see for example [1]- [6]) that different signals are most informative for different faults: vibration signals are well suited for monitoring bearing faults [1], [2], current signals are good for detecting problems such as broken rotor bars or eccentricity relatedfaults [1], [3] and capacitor sensors may be used to measure the partial discharges that are indicative of stator winding insulation problems [1], [4].…”
Section: Introductionmentioning
confidence: 99%